Development of Multi-Layered Kenaf (Hibiscus Cannabinus L.) Board Using Core and Bast Fibres - Ab. Wahab, Nor Hafizah (2007)
Kenaf (Hibiscus cannabinus L.) is relatively a new crop in Malaysia. This fast growing species has been choosen and introduced in Malaysia to ensure a continuous supply of raw material for the composite industry, and as alternative solution for the shortage in rubberwood supply. An attempt was made to develop a multi-layered kenaf board (MLKB) utilising different parts of kenaf stem: bast, core and a combination of bast and core fibres. The objectives of this study were: 1) to evaluate methods of retting and separating of kenaf fibres (bast and core fibres) for kenaf board production, 2) to determine the effects of resin content and bast to core proportion on the physical and mechanical properties of MLKB, and 3) to determine the properties of kenaf board with woven-bast mat as core. The kenaf bast and core were separated manually. The retting process (to separate bast fibres from the pectic materials) was carried out by submerging the bast in either cold water or alkali (NaOH) at certain duration. Three levels of alkali concentration were used: 1, 3, and 5%. The crude bast fibres were than combed and washed several times until straight and silky fibres were produced. The core portion was chipped into ≤ 2 cm size particles. Both bast fibres and core particles were then dried to about 5% moisture content. Multi-layered kenaf boards were fabricated using urea formaldehyde (UF) and melamine urea formaldehyde (MUF) resins as binders. Four types of 0.50 g/cm3 density MLKB were made with varying bast : core proportions. Homogenous particleboards utilising 100% rubberwood particles were used as control. Since bast fibres have low wettability, a low molecular weight phenol formaldehyde (LPF) resin was used to pretreat the bast fibres prior to normal blending with either UF or MUF resin. An attempt was also made to produce a kenaf board with woven bast fibre mat as core. The properties of boards were tested using MS standards 1737: 2005. Data were subjected to Analysis of Variance (ANOVA) and the effects were further analysed by means separation using Least Significant Difference (LSD) at p ≤ 0.05. The study indicates that treatment of kenaf bast with different alkali concentrations significantly affected the properties of kenaf bast fibres such as fibre and lumen diameter, cell wall thickness and chemical components. Kenaf bast fibres that have been treated with 5% NaOH gave the lowest amount of holocellulose, hemicellulose, α-cellulose, and lignin (48.7%, 29.7%, 19.0%, and 8.5% respectively.) High yield of holocellulose was obtained for treatment with water alone. Both the kenaf core and rubberwood have similar buffering capacity which is more sensitive towards acid. Bast fibre, on the other hand is more sensitive towards alkali. Due to its morphological properties, kenaf core inner surface exhibited higher wettability than outer surface. Kenaf board comprising bast materials in the middle layer were stiffer than that of homogeneous 100% rubberwood. The incorporation of LPF resin in the fibres of MUF-bonded board comprising 70% kenaf core on the surface and 30% bast in the middle layer produced boards of reasonably good strength and dimensional stability. The modulus of elasticity (MOE) was 873 MPa, modulus of rupture (MOR) 8.9 MPa, internal bonding (IB) 0.32 MPa, thickness swelling (TS) 12.6%, and water absorption (WA) 118.9%. The presence of bast long fibres had improved the linear expansion (LE) length-wise by about 16.2%. All the kenaf board have higher MOR than that of 100% rubberwood. The woven technique applied to improve the performance of the MLKB was found to be effective, producing 8.2% stronger and 22.3% stiffer board. The IB was also improved by 61.9%. The dimensional stability of these boards was superior to that of MLKB. Boards having 100% kenaf core consistently gave superior performance in mechanical strength but relatively poor in TS and WA due to the high porosity and absorbent of the core itself. The linear regression between IB and strength showed higher R2 values were obtained for all boards containing bast fibres compared to those having 100% core particles. The lack of fibre bonding among the bast fibres was found to be the dominant factor affecting the performance of woven-layered kenaf board (WLKB).